Facile synthesis of aquo-cisplatin arsenite multidrug nanocomposites for overcoming drug resistance and efficient combination therapy. (22nd November 2018) - Xin, Jingyu; Zhang, Ke; Huang, Jiaqi; Luo, Xiangjie; Gong, Xuanqing; Yang, Zhaoxuan; Lin, Hongyu; Shan, Hong; Gao, Jinhao
Abstract : An aquo-cisplatin arsenite multidrug nanocomposite loaded with cisplatin and arsenic trioxide prodrugs was reported for overcoming drug resistance and combination therapy. Abstract : Cisplatin (CDDP) and arsenic trioxide (ATO), two representative inorganic anticancer drugs, have been successful in the treatment against several kinds of malignancies. However, combination therapy with these two drugs in clinical application suffers from poor pharmacokinetics, serious side effects, and drug resistance of the tumor. Herein, we report a carrier-free aquo-cisplatin arsenite multidrug nanocomposite loaded with cisplatin and arsenic trioxide prodrugs simultaneously. This nanocomposite achieves a high loading capacity and pH-dependent controlled release of the drugs. Because of these features, this nanocomposite shows better in vitro toxicity against various carcinoma cell lines than either the single drug or free drug combination, promotes the synergistic effect of cisplatin and arsenic trioxide, and significantly inhibits the growth of tumors in vivo . Furthermore, cisplatin and arsenic trioxide in this nanocomposite can realize a coordination of both enhanced DNA damage and DNA repair interference within cisplatin-resistant cells, which results in overcoming the drug resistance effectively. Gene expression profiles demonstrate the reduced expression of proto-oncogenes and DNA damage repair related genes MYC, MET, and MSH2, along with the increase of tumor suppressor genes PTEN, VHL, and FAS after the nanocomposite treatment. This type of multidrug nanocomposite offers an alternative and promising strategy for combination therapy and overcoming drug resistance.